We can solve this system of equations using the substitution method.
First, rearrange the first equation to solve for x in terms of y:
-x + 6y = 13
-x = 13 - 6y
x = -13 + 6y
Now, substitute this expression for x into the second equation:
4(-13 + 6y) - 10y = -10
-52 + 24y - 10y = -10
14y = 42
y = 3
Now that we have found the value of y, we can substitute it back into the expression for x in terms of y:
x = -13 + 6(3)
x = -13 + 18
x = 5
Therefore, the solution to the system of equations is x = 5 and y = 3.
–x+6y=13
4x–10y=–10
1 answer